PERANAN PERBANKAN DALAM MENINGKATKAN PEREKONOMIAN INDONESIA - Windy Mahrani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Indonesia as a developing country, has the aim of creating a just and prosperous society materially and spiritually. With the established strategy, Indonesia seeks to implement various steps to strengthen its economy and secure equitable development throughout the archipelago. BUMN is one of the main drivers of the national economy. As part of a state-owned company, the banking sector does not only carry out operational activities to gain profits, but also to support the government's efforts to advance the country's economy. This is clearly confirmed in Article 4 of Law of the Republic of Indonesia Number 7 of 1992 concerning Banking which states that the aim of Indonesian banking is to support national development in order to increase equality, economic growth and national stability for the welfare of the general public.